Comparison of Percentage Depth Doses with the Published Data for Co-60 Radiotherapy Machine at a Regional Cancer Hospital - Ali, Javaid; Sohail, Muhammd; Samad, Abdul; Ahmad, Israr; Soomro, Hafeezullah; Biradar, Ghufran; Naz, Irum; Tariq, Imadullah (Diponegoro University Semarang Indonesia, 2023)
In external beam radiation therapy, the percentage depth dose (PDD) is a main factor for estimation of patient’s dose and dose distribution in target volume, therefore its accurate estimation is important. The purpose of this article is to compare PDDs with the published PDDs of different authors along central axis at different depths and field sizes for cobalt-60 (Co-60) radiotherapy machine at a regional cancer hospital Pakistan. A dedicated water phantom was used for estimation of PDDs at different depths and different field sizes, for Theratron phoenix Co-60 machine. It was observed that for 10×10 cm2 filed size of Co-60 beam mean percent variation in measured PDDs and published PDDs by different authors was -0.29% to 1.13%, which was within acceptable limit of ± 2%. However, for one author who used semi-empirical equation for PDDs calculation, the mean percent variation between measured PDDs and that of the author was -3.23%, 4.69% and 5.88% for 10×10 cm2, 25×25 cm2 and 30×30 cm2 field sizes of Co-60 beam respectively, which were within acceptable limit of ±10%. A noticeable increase in PDDs was observed with increase of the field size at given depth which shows obvious contribution of secondary scattered radiation. Also measured PDDs were well matched with that of published PDDs of most of the authors i.e. ± 2%, but the measured PDDs were moderately matched with that of PDDs for only one author for some field sizes and some depths i.e. ±10%, which need to be rectified by taking more such data.